Pengembangan Program Aplikasi Analisis Pelat 2D dengan Metode Finite Difference Menggunakan Matlab - Alexander B.S. Malik; Remigildus Cornelis; Ruslan Ramang (Universitas Nusa Cendana, 2022)
The rapid development of construction technology has an impact on application programs that are created to facilitate the calculation of structures in buildings, especially in designing plates in buildings. Program applications such as SAP 2000 software are often used in structural calculations but are costly. This study develops MATLAB to produce an application program for analyzing and modeling numerical data based on the matrix concept. The method used is the finite difference method which is a numerical approach method based on partial differential equations. This application program was developed by calculating the deflection, moment, and stress, which are displayed in the form of contour. This program was designed with the equations entered into the coding for each of the existing models. Then the results obtained are compared with the results of the calculation of the plate moment on PBI-1971.